Revealing the paradoxes of horsemeat – The challenges of marketing horsemeat in Finland - Jaskari, Minna-Maarit; Leipämaa-Leskinen, Hanna; Syrjälä, Henna (Association of Business Schools Finland, 2015)
This study aims to analyse the different cultural meanings attached to horsemeat consumption in the context of the Finnish market. We take the “meat paradox” as a theoretical starting point and investigate the underlying cultural structures that guide consumers’ meaning-making and consumption decisions in regard to horsemeat. The data were generated after the horsemeat scandal, drawing on a wide variety of media texts about horsemeat consumption. The data were analysed through qualitative content analysis and the findings reveal five horsemeat paradoxes. Each paradox contains meanings that reflect both the justifications for and avoidance of eating horsemeat. The findings show how horsemeat consumption holds various and even contradictory meanings, elucidating how it may be difficult for consumers to take a stand towards eating horsemeat. Thereby, the study provides novel ideas for marketing that are grounded in our deep-rooted and ingrained cultural understandings.
Keywords: cultural meanings; horsemeat; meat consumption; marketing; fi=Markkinointi|en=Marketing|